2015
DOI: 10.3414/me13-02-0038
|View full text |Cite
|
Sign up to set email alerts
|

Decision Making Concepts for the Remote, Personalized Evaluation of COPD Patients’ Health Status

Abstract: SummaryIntroduction: This article is part of the Focus Theme of Methods of Information in Medicine on “Biosignal Interpretation: Advanced Methods for Neural Signals and Images”.Objectives: This paper presents the main concepts of a decision making approach for the remote management of COPD patients based on the early detection of disease exacerbation episodes.Methods: An e-diary card is defined to evaluate a number of physiological variables and clinical parameters acquired remotely by means of wearable and en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 29 publications
0
17
0
Order By: Relevance
“…We found that there were a high percentage of patients who were not interested in participating. While telemonitoring studies have not consistently reported their recruitment rate [ 18 , 19 ], our recruitment rate was lower than the rate found in the custom COPD wristband study (16% vs 57%) and our dropout rate was higher (43% vs 22%) [ 17 ]. This may have been due to privacy concerns of recording audio or the differences in recruitment settings, as one of our sources of patients was hospitalized patients who were often too sick to participate.…”
Section: Discussionmentioning
confidence: 61%
“…We found that there were a high percentage of patients who were not interested in participating. While telemonitoring studies have not consistently reported their recruitment rate [ 18 , 19 ], our recruitment rate was lower than the rate found in the custom COPD wristband study (16% vs 57%) and our dropout rate was higher (43% vs 22%) [ 17 ]. This may have been due to privacy concerns of recording audio or the differences in recruitment settings, as one of our sources of patients was hospitalized patients who were often too sick to participate.…”
Section: Discussionmentioning
confidence: 61%
“…This is going to be an important future direction and challenge in patients with COPD breathing spontaneously. 68 70 …”
Section: Discussionmentioning
confidence: 99%
“…The monitoring of PROs would seem to be a mutual responsibility between the professionals and patients. Indeed, the benefits of self-monitoring have already been demonstrated: patients with chronic obstructive pulmonary disease and in patients with cerebral palsy were able to detect relevant changes in their health condition [22], which reduced long-term complications [23].…”
Section: Personal Feedback Enhances Individual Grip On Spasticitymentioning
confidence: 99%